2002
DOI: 10.1046/j.1365-246x.2002.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure variation from the Precambrian to Palaeozoic platforms in Europe imaged by the inversion of teleseismic receiver functions-project TOR

Abstract: S U M M A R YThe TOR experiment (Teleseismic TOmography TORnquist) carried out in winter 1996/97 across the Trans-European Suture Zone (TESZ) in Germany, Denmark and Sweden has collected new data to investigate the transition zone between Precambrian and Palaeozoic Europe. In this study, seismograms of teleseismic earthquakes recorded by the broad-band TOR stations have been used to calculate the receiver functions. The time-domain inversion method has been applied to the receiver functions to compute S-wave v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…However, the result of inversion depends on the starting model, in particular for noisy data. In order to receive independent results, we can run the inversion with many different starting models and then stack the results to calculate one mean model of the structure (e.g., Wilde-Piórko et al 2002). Forward modeling using trial-and-error method may find a simple model which could well explain the observed receiver functions.…”
Section: Discussion Of the Deviations Uncertainties And Errorsmentioning
confidence: 99%
“…However, the result of inversion depends on the starting model, in particular for noisy data. In order to receive independent results, we can run the inversion with many different starting models and then stack the results to calculate one mean model of the structure (e.g., Wilde-Piórko et al 2002). Forward modeling using trial-and-error method may find a simple model which could well explain the observed receiver functions.…”
Section: Discussion Of the Deviations Uncertainties And Errorsmentioning
confidence: 99%
“…The solution of the inverse problem can be affected by the starting model [Ammon et al, 1990] where an improper choice may steer the solution toward a local minimum. In addition to performing a series of inversions with perturbed starting models [Ammon et al, 1990;Mangino et al, 1993;Wilde-Piórko and Grad, 2002], we conduct a global solution search in model space based on the genetic algorithm (GA) [Shibutani et al, 1996]. This method simulates gene evolution in biological systems and solves nonlinear inverse problems through complete global optimization [Sambridge and Drijkoningen, 1992].…”
Section: 1002/2014jb011353mentioning
confidence: 99%
“…Many studies already exist for this experiment using a range of seismological methods. Besides an overview of the experiment given by Gregersen et al (2002), among the studies are a teleseismic P tomography (Arlitt et al 1999), non‐linear P and S tomography studies (Shomali et al 2006; Voss et al 2006), receiver function studies (Gossler et al 1999; Wilde‐Piórko et al 2002; Alinaghi et al 2003) and anisotropy analyses (Wylegalla & TOR Working Group 1999; Plomerova & TOR Working Group 2002). However, none of the named studies used absolute traveltimes.…”
Section: Datamentioning
confidence: 99%